Navigating cross-cultural boundaries: translation strategies for culture-loaded words in Chinese Yu opera - Liu, Yi; bin Abdullah, Muhammad Alif Redzuan; bin Syed Abdullah, Syed Nurulakla (Human Resources Management Academic Research Society (HRMARS), 2024)
The translation of culture-loaded words is crucial in cross-cultural communication, particularly in traditional Chinese Yu Opera, which contains rich cultural nuances. Proper translation ensures the preservation of authenticity and accessibility for a global audience. Despite extensive research in other fields, the study of culture-loaded words in Yu opera translation remains scarce, highlighting the need to address this gap. This study employs a comparative analysis of the source text (ST) and target text (TT) to identify the translation strategies used by the translator. Additionally, a semi-structured interview with the translator was conducted to understand the rationale behind the chosen strategies. This dual approach allows for a comprehensive examination of the translation process and the factors influencing strategy selection. Key findings reveal that domestication is more prevalent and effective than foreignization in navigating cultural boundaries. The study highlights that the choice of translation strategy is significantly influenced by both social factors, such as the interests of different parties, and individual factors, including the translator’s subjectivity. Further research could explore the impact of different cultural contexts on translation strategies in traditional opera, conduct comparative studies across local operas, and investigate audience reception and translator training to enhance cultural sensitivity and translation quality.